El control interno y la gestión de tesorería en la Municipalidad Distrital de San Juan Bautista, periodo 2022 - Nuñez Garcia, Denisse Margarita (2023)
Internal control is presented as a useful management tool for a better organization in the work area, since it exercises transparency control in work activity, ensuring reliability in the proper management of state resources. The main objective of this research is to determine the relationship between internal control and treasury management in the district municipality of San Juan Bautista, Period 2022. Being of a descriptive correlational type, developed through a non-experimental design, having as a study population 205 workers. The investigation determined the characteristics of internal control, being mostly Good at 63.43%, Regular at 21.64% and Bad at 14.93%, on the other hand Treasury Management is mostly Good at 51.49%, Regular at 21.64% and Bad in 14.93%, likewise the Spearman's Rho Correlation Coefficient R=0.713 and the Bilateral significance level Sig.=0.000 were found to be less than 5%, indicating that it is significant, so it is concluded that there is a positive relationship between internal control and treasury management in the district municipality of San Juan Bautista, Period 2022.